JURIDICAL ANALYSIS OF CONSTITUTIONAL COURT DECISIONS NO. 18/PUU-XVII/2019 RELATED TO THE "LEASING" ANnotATION CAN STILL WITHDRAW COLLATERAL - Sunardi, Sunardi; Rokhim, Abdul; Nafta, Ijtihada Mahirata (International Significance of Notary, 2022)
The Constitutional Court's decision regarding the withdrawal of goods by leasing must go through the courts. according to MK spokesman Fajar Laksnono who stated that the contents of the Constitutional Court's decision "... there may no longer be withdrawals of leasing goods directly to creditors,". In addition, it also contains, "If there is a breach of contract or default, the execution of the fiduciary guarantee cannot be carried out by the fiduciary recipient (creditor), but must submit an application to the District Court,". It is this decision that makes pros and cons and makes its own interpretation. Regarding the "leasing" annotation, you can still withdraw. 18/PUU-XVII/2019 Regarding the "Leasing" Annotation You Can Still Withdraw Fiduciary Guarantees. And the Legal Consequences of the Constitutional Court Decision Regarding Fiduciary No. 18/PUU-XVII/2019, can creditors still carry out direct execution of fiduciary guarantees? By using the normative juridical research method, the results of the Juridical Analysis of the Constitutional Court's Decision on Fiduciary No. 18/PUU-XVII/2019 Regarding the "Leasing" Annotation You Can Still Withdraw Fiduciary Guarantees. Withdrawal of Leasing Goods Must Go Through Court”. stated that the contents of the Constitutional Court's decision "... there may no longer be withdrawals of leasing goods directly to creditors,". In addition, it also contains, "If there is a breach of contract or default, the execution of the fiduciary guarantee cannot be carried out by the fiduciary recipient (creditor), but must submit an application to the District Court,". You Can Still Withdraw Fiduciary Guarantees as long as the execution is carried out based on Article 29, Article 30 and Article 31 of the Fiduciary Law and is subject to other relevant laws and regulations, including but not limited to POJK 035/POJK.05/2018. And the Legal Consequences of the Constitutional Court Decision Regarding Fiduciary No. 18/PUU-XVII/2019 That is, whether creditors can carry out direct execution of fiduciary guarantees. leasing in withdrawing fiduciary guarantees and changing the way to deal with problems arising from bad loans can be done in two ways, including the following: 1) Non Litigation 2) Litigation OJK has also issued regulations related to the execution of collateral objects by Financing Companies, including: 1 ) Based on the provisions of Article 21 to.d. Article 23 and Article 51 of the Financial Services Authority Regulation Number 29/POJK.05/2014 concerning the Conducting of a Financing Company Business, stipulate provisions concerning the imposition of fiduciary guarantees by Financing Companies. 2) Based on the provisions of Article 49 of the Financial Services Authority Regulation Number 30/POJK.05/2014 concerning Good Corporate Governance for Financing Companies, a cooperation mechanism has been set up between Financing Companies and other parties to perform the collection function to debtors.Keywords: Constitutional Court Decision, Leasing, Fiduciary Guarantee.